Modification data attack inside computer systems: a critical review - Vahid Kaviani J; Parvin Ahmadi Doval Amiri; Farsad Zamani Brujeni; Nima Akhlaghi (Computer Science and Information Technologies, 2020)
This paper is a review of types of modification data attack based on computer systems and it explores the vulnerabilities and mitigations. Altering information is a kind of cyber-attack during which intruders interfere, catch, alter, take or erase critical data on the PCs and applications through using network exploit or by running malicious executable codes on victim's system. One of the most difficult and trendy areas in information security is to protect the sensitive information and secure devices from any kind of threats. Latest advancements in information technology in the field of information security reveal huge amount of budget funded for and spent on developing and addressing security threats to mitigate them. This helps in a variety of settings such as military, business, science, and entertainment. Considering all concerns, the security issues almost always come at first as the most critical concerns in the modern time. As a matter of fact, there is no ultimate security solution; although recent developments in security analysis are finding daily vulnerabilities, there are many motivations to spend billions of dollars to ensure there are vulnerabilities waiting for any kind of breach or exploit to penetrate into the systems and networks and achieve particular interests. In terms of modifying data and information, from old-fashioned attacks to recent cyber ones, all of the attacks are using the same signature: either controlling data streams to easily breach system protections or using non-control-data attack approaches. Both methods can damage applications which work on decision-making data, user input data, configuration data, or user identity data to a large extent. In this review paper, we have tried to express trends of vulnerabilities in the network protocols’ applications.